2022
DOI: 10.3389/fmed.2022.962094
|View full text |Cite
|
Sign up to set email alerts
|

Graft survival differences in kidney transplants related to recipient sex and age

Abstract: BackgroundIn recent years, there has been increasing interest in studying differences in recipient sex in renal disease treatment, access to renal replacement therapy, and subsequent outcomes. Our aim was to find out whether there are differences in outcomes after renal transplantation between female and male kidney transplant recipients in our series, particularly in adults under 60 years of age during long-term follow-up.MethodsThis was a retrospective study of our kidney transplant series (n = 1,101) to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…It should be noted that the Taiwanese study included KT between 1988 and 2009, which was earlier than the last period in the present study. A recent study from Spain [ 18 ] showed lower graft survival for women under 60 years of age, which is more consistent with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…It should be noted that the Taiwanese study included KT between 1988 and 2009, which was earlier than the last period in the present study. A recent study from Spain [ 18 ] showed lower graft survival for women under 60 years of age, which is more consistent with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the data is contradictory and an association between male sex and declining eGFR is not clear in our dataset. Furthermore, strong evidence suggests that younger females are at higher risk of graft loss ( 59 61 ), which contradicts the results linking male sex to a sharper decline in kidney transplant function.…”
Section: Discussionmentioning
confidence: 90%
“…Over 45 years, the risk persisted but it was reduced to HR 0.95 (95% CI, 0.91–0.99). A decreased immune response associated with postmenopausal hormonal changes, adherence and reduced body mass were mentioned as explanations ( 34 ) Finally Sancho et al ( 35 ), in a retrospective study over one thousand patients, found that gender did not have an impact on graft outcomes. Chronic rejection in women and death with functioning graft were main reasons for graft loss.…”
Section: Outcome After Ktmentioning
confidence: 99%